Pengaruh Metode One Day One Page Terhadap Keterampilan Membaca Sekilas pada Buku Dongeng Kelas 5 Sekolah Dasar - Efania, Nur Afni; Umam, Nanang Khoirul (Jurnal Simki Pedagogia, 2023)
The low implementation of literacy activities for students makes researchers want to develop reading literacy activities for students. The purpose of this research is to develop a school literacy movement using the one day one page method, to improve students' speed reading skills. This activity familiarizes students with reading books for 15 minutes at the beginning of learning. The school literacy movement has three stages, namely the habituation stage, the development stage, and the learning stage. The books used in this literacy movement are folklore books. The implementation of literacy activities in cycle II meetings 1 and 2 resulted in an increase in student activity in literacy activities, as well as an increase in the ability to understand skimming techniques and the level of student confidence. students also find it easier to complete some of the test questions that the teacher has given. Compared to cycle I, meeting 1 did not increase student activity. Applying the skimming technique using the one day one page method can improve the ability to understand narrative texts and also improve reading literacy skills in class V UPT SDN 22 Gresik. This study uses a qualitative research method with a qualitative descriptive approach.